Mispersepsi Kewajiban dan Hak Suami Istri di Masa Pamdemi - Suhajis (Moderasi : Journal of Islamic Studies, 2022)
This paper explains the importance of avoiding misperceptions between husband and wife's rights and obligations during a pandemic. The life of husband and wife requires the fulfillment of the obligations and rights of each partner. The lack of satisfaction of each partner can trigger household disharmony to the point of causing divorce, especially the Covid-19 pandemic condition which causes life instability in several aspects. This research is a literature and conceptual study. The results of the analysis show that first; it is necessary to strengthen communication that is increasingly intense for married couples due to the negative impact of the covid-19 pandemic; second; Understanding religion is the main foundation in achieving household harmony.